The Role of Strategic Human Resource Management Practices in Fostering Social Sustainability - Bentota Arachchige, Dharani (My University, 2026)
The focus of sustainability has been expanding beyond the economic and environmental aspects. The companies find it complex in balancing the economic performance with the ethical responsibility because of the popularity of the new norm which is social sustainability. Strategic human resources management (strategic HRM) depicts as a strategic driver of the company and plays an important role in supporting in integrating social sustainability into HR practices. This study explores how well the strategic HRM practices contribute as a key driver of social sustainability. This study has been conducted in a qualitative approach, utilizing semi structured interviews. In order to elaborate strategic HRM, AMO framework was incorporated and studied under three core aspects, ability, motivation and opportunity. The ability enhancing aspect included recruitment and selection and training and development while motivation aspect compromised with compensation, performance evaluation and performance management. The opportunity aspect discusses about job design and job evaluation. Having successful implementation of strategic HRM practices on the key areas, depicts the societal outcomes such as trust, justice, wellbeing and participation, this study highlights on how such practices contribute to individual social sustainability outcomes. The findings of this thesis reveal on how the ability, motivation and opportunity enhancing aspect of strategic HRM foster social sustainability across four pillars namely equity, social capital, participation and influence and well-being. It also provides a holistic view on how the AMO facets interdependent while providing results in terms of social sustainability. The right combination of strategic HRM practices inline with AMO framework provides a favourable environment for employees to work with. These practices not only create work life balance but also provide positive energy enhancing quality of work life and motivation. The results of these aspects tend to be visible strategically by achieving long-term organizational goals. Therefore, the findings suggests that strategic HRM plays a vital role supporting companies to build upon a workplace with wellbeing equity and employability while being a regenerative asset supporting the employees.
Keywords: Strategic HRM; Social Sustainability; Equity; Social Capital; Well-being; Participation; Social Justice